The movement for a society of peace: Islamism and political sense-making in post-conflict Algeria - Sakthivel, VS (2019)
This thesis seeks to broadly understand the role of social meaning-making in the formation, practices, and discourses of political challengers. Focusing on the case of Islamism in Algeria, I highlight how collective efforts to make sense of the 1989 political opening and the 1990s civil conflict have re-introduced into public contestation: the meaning of Islamist moderation, the role of religion in politics, Algerianness/nationalism, and the viability of political parties. Using ethnographic research focused on Algeria’s Muslim Brotherhood affiliate, the Movement for a Society of Peace (MSP) party, I show that such contested concepts factor prominently in how movement identity is negotiated and political platforms are articulated, both by the leadership in order to position itself as a viable political actor, and by the movement base so they may reconcile their multiple subjectivities. I argue that Algerian Islamists do not reject the wider political culture that disavows their brand of politics or the attendant hegemonic frames used to cast them out of the body politic; instead, they work to make their positions and their activism legible, palatable, and even meaningful through these very frames. This argument interrogates the assumption common in academic literature that Islamism is at odds with local and nationalist articulations of subjecthood.